Model calculation of charged galactic cosmic ray radiation dose during a flight to Mars - Lyu, Dan; Qin, Gang (Frontiers in Physics, 2025)
The radiation exposure from galactic cosmic rays (GCRs) presents a significant challenge for human spaceflight to Mars. In this study, we employ our previously published GCR radiation dose calculation model to estimate the GCR radiation dose rates during a Mars mission from the Earth. Using this model, we calculate the absorbed dose rates of GCRs during the flight to Mars and compare our results with observational data from the Mars Science Laboratory Radiation Assessment Detector (MSL-RAD) and computational results from the Badhwar-O’Neill (BON) GCR model. First, we compute the energy spectrum of GCRs during the Earth-to-Mars transit using the GCR modulation model. Then, using the fluence-to-dose conversion coefficients (FDCCs) from ICRP 123, the absorbed dose rates of 15 human organs/tissues during the Earth-to-Mars transit are calculated to represent the general absorbed dose rate of the body (in water). Furthermore, considering the contributions of different elements and the underestimation of the model in 2012, we calculate the total absorbed dose rates of charged GCRs in silicon during the flight. Our results generally align with the BON11 model (excluding pions) and are consistently ∼20% lower than the central value of the MSL-RAD/B observational data within expected uncertainties. This work may provide help for the future mission with radiation protection.